Modified enrichment-serology procedure for detection of salmonellae in soy products. - Surdy, T E (1981)
A modified enrichment-serology (MES) procedure was used to reduce the time necessary for salmonella analysis. Naturally contaminated samples of soy products were preenriched in 1% proteose peptone for 6 h at 37 degrees C followed by inoculation into tetrathionate broth for 18 h at 37 degrees C. Two drops of the tetrathionate sample were inoculated into M broth. After incubation at 37 degrees C for 6 h, 0.85 ml of the mixture was formolized, and 0.1 ml of polyvalent H antiserum was added. After incubation in water bath at 50 degrees C for 1 h, the appearance of a typical floccular flagellar precipitate was observed in tubes positive for salmonellae. Over 3,000 samples were subjected to standard biochemical and serological procedures, and the results were compared with those of the MES method with a 96.7% correlation. Eleven of the samples (0.3%) were false-negative with the MES procedure, and 3% were false-negative with the U.S. Food and Drug Administration Bacteriological Analytical Manual procedure. The 3% negative samples by this latter procedure were subsequently found to be positive by the MES procedure. The MES procedure reduced the time required for salmonella analysis from 4 days to 32 h.